Principles of Entrepreneurship: Social Media Portfolio (ENT530) MMGAmazing / Irrawanita Kamaruddin - Kamaruddin, Irrawanita (2018)
Through this project, I was given exposure on how to set up real entrepreneurial business using its own structure and concept. Basically to create a virtual business so I need to register the real entrepreneurial business with the Companies Commission of Malaysia (SSM). Through this real entrepreneurial business I use social media platform by utilizing Facebook (FB) for marketing purpose. As a purposed marketing channel, I use my existing FB personal to realize the Fecebook (FB) page for this entrepreneurial business. My customing URL Facebook (FB) page is https://www.facebook.com/irrawanita. I introduced the initial picture of my product, the modern massage oil of Marvelous Massage Gel by Sarwa Jannah using teaser post. Next through soft sell without introducing goods or products and finally I introduce the product directly through hard sell.